MY SAY: End of the road for the Walkman - Abd Razak, Dzulkifli (2010)
It was one of the most innovative inventions of its time, and lasted for more than a generation. Some 30 years ago, the Walkman — a portable audio cassette player — burst onto the world stage, thanks to Sony, one of the world's most creative electronics companies. But like all things, there is always an expiry date, and for the Walkman, it came quite unexpectedly on Oct 28 this year.